RE: Emphysematous pyelonephritis: is nephrectomy warranted? - Kamarulzaman, Mohd Nazli; Che Mohamed, Siti Kamariah (Wolters Kluwer - Medknow Publications, Wolters Kluwer India Pvt. Ltd., 2016)
We read with great interest the article “Emphysematous pyelonephritis: Is nephrectomy warranted?” by Alsharif M. et al .[1] This article highlights interesting updated in managing emphysematous pyelonephritis (EPN) from radical surgery to medical management. Similar finding was published earlier by Ubee SS et al. in their literature review. [2] They noted the trend towards medical management was begun since late 1980s. This change in management trend was associated with improve in mortality from 40-50% in 1970s to 13.5% recently. [2] It was similar in this paper which had the rate of 30% and 100% for overall mortality and radical nephrectomy rate respectively. This trend of management seems to be widely accepted all over the world. In our opinion, early nephrectomy had its own rule in managing EPN, especially in case where the renographic clearance is <10%.[3] The percentage of EPN patients undergone surgery will be markedly reduced with early detection and aggressive medical management. However, the comparison between medical management and early nephrectomy in term of mortality cannot be ascertained except similar group of EPN patient being subjected for each arm of treatment options. Patients with multiple co-morbidities and in sepsis certainly had higher mortality rate regardless of whatever treatment given.